Efektivitas Quick Response Code Indonesian Standard Sebagai Metode Pembayaran Nontunai Suroboyo Bus - Romy Hafizh Lesmana; Agus Widiyarta (Mahesa Research Center, 2022)
This article aims to find out and analyze the effectiveness the non-cash payment method program uses the Quick Response Code Indonesian Standard (QRIS) on Suroboyo Bus. Suroboyo Bus was first launched in 2018 using plastic bottle waste as a payment method, but since the statute of Surabaya’s Major through Peraturan Walikota Number 56 Year 2021, there has been a change in the status of the Unit Pelaksana Teknis Dinas Pengelolaan Transportasi Umum (UPTD PTU) which is the implementing unit of Suroboyo Bus under the Dinas Perhubungan Kota Surabaya has become a Badan Layanan Umum Daerah(BLUD), making Suroboyo Bus financial management more flexible, making it possible to use non-cash payment methods using QRIS. The problem is focused on using QRIS as a non-cash payment method on Suroboyo Bus. In order to approach this problem is using the theory program’s effectiveness by Budiani, which consists of 1. The accuracy of program targets; 2. Program socialization; 3. Program Objectives; and 4. Program Monitoring. The data were collected through interviews, observations and documentation and analyzed with qualitative methods. This study concludes that the use of QRIS is quite effective, but the public's interest in using QRIS is still low so it needs to be socialized and adjusted to the conditions of the society.